Peningkatan kualitas sumber daya manusia pada perbankan syariah - A'yun, Qurrota (Maliki Interdisciplinary Journal, 2024)
This research aims to alternatives to be used to improve the quality of human resources (HR) in the Islamic banking industry. Human resource problems are one of the challenges faced by Islamic banks. Improving the quality of human resources in Islamic banks requires effective management. In this article, qualitative analysis is used through a literature observation approach. By analyzing several articles regarding HR management, the author found relevant discussions. The research results show that training, development, and education about HR and its implementation are needed to improve the quality of HR management in Islamic banks. Apart from that, certification is also needed because it is difficult to compete in the era of globalization without proof of membership.